The geography teaching in perspective inclusive education - Ramos, Ana Carolina; Martins, Rosa Elisabete Militz Wypyczynski (Geosaberes; Vol 8 No 15 (2017): May - Aug, 2017)
The present research carried out in the form of a graduation work in Geography of FAED/UDESC is located in contributing to teaching and learning in Geography, based on the perspective of Inclusive Education, aimed at analyzing how students appropriate Contents and concepts of Geography. We chose a qualitative study with a case study approach, carried out in an 8th grade class in a public school in the city of Florianópolis/SC. The research took place in four stages that were fundamental to understanding how students with disabilities follow the teaching-learning process. The use of workshops with board games became relevant, since there was a concern to work with diverse activities in the process of geographic education, in order to overcome barriers of learning.
Keywords: Educação Inclusiva, ensino de Geografia, oficina pedagógica.